RELEVANSI AYAT-AYAT TENTANG POLITIK DALAM AL-QUR’AN DENGAN KONSTITUSI DI INDONESIA: Tematik Pancasila, UUD 1945 dan Pasal-Pasal Kontroversial KUHP - Ashari Mujamil; Ali Wafa (istinbath, 2023)
The Qur'an has become a universal guide to life - including political ethics - although it is not explained explicitly so that in its development, the concept of politics and government reflected in the constitution often has relevance to the values of the Qur'an. This study aims to reflect on the main values in the al-Qu'an related to political ethics to be elaborated in the concept of the Constitution in Indonesia, namely Pancasila and the UUD 1945. This research analyses the result using a qualitative approach, a thematic literature study method aided by Abdullah Saeed's contextual hermeneutic approach. The research results show that as a whole, the Pancasila precepts have a meaning that is relevant to the values of the Qur'an, namely the 1st precept of monotheism, the 2nd precept of equality, the 3rd precept of brotherhood/ unity, the 4th precept of deliberation in the process of decision-making, and the 5th precept of social justice/welfare. As for the thematic review of the UUD 1945, there are basic values of political ethics in the Qur'an, namely regarding law, power, and sovereignty; leadership and democracy; government apparatus; and Human Rights. Regarding the controversial articles in the Criminal Code, there are several important points, including the limitations on freedom of expression, alternative criminal penalties and commutation of sentences for corruptors, as well as punishment for adultery perpetrators, which in the contextualization of the values of the Quran contains the relevance of ethical, political and moral values.